Structural alterations of the choroid evaluated using enhanced depth imaging optical coherence tomography in patients with coronavirus disease - Kocamış,Özkan (2022)
ABSTRACT Purpose: To assess choroidal changes using enhanced depth imaging optical coherence tomography in coronavirus disease (COVID-19). Methods: Thirty-two patients with moderate COVID-19 and 34 healthy subjects were included in the study. Choroidal thickness was measured at 3 points as follows: at the subfovea, 1500 mm nasal to the fovea, and 1500 mm temporal to the fovea. The total choroidal area, luminal area, stromal area, and choroidal vascular index were measured with Image-J. All the measurements were performed during the disease and at 4 months after remission. Results: In the patient group, the subfoveal, nasal, and temporal choroidal thicknesses were decreased as compared with those in the controls, but without statistically significant differences (p=0.534, p=0.437, and p=0.077, respectively). The mean total choroidal, stromal, and luminal areas and choroidal vascular index were statistically significantly decreased in the patient group (p<0.001, p=0.001, p=0.001, and p=0.003; respectively). At 4 months after remission, the choroidal structural parameters and choroidal vascular index revealed statistically significant increases as compared with the baseline measurements in the patients with COVID-19 (all p<0.001 and p=0.047, respectively). Conclusion: The choroidal vascular and stromal parameters showed significant transient decreases during the disease course of COVID-19.